A morphometric study on the articulating facets of talus in North Indian population - Garg, Shavi; Verma, M/s Usha; Suri, Arpita; Aulakh, Kirandeep Kaur (Asian Journal of Medical Sciences, 2021)
Background: Morphometry of talus will be helpful for radiologists, orthopaedicians and surgeons for diagnosis and treatment of talar fractures and making bone prosthesis. Aims and Objectives: The purpose of our study is to do a morphometric analysis of talus to facilitate orthopedicians in planning surgeries for subtalar implants and foot prostheses. This will be of great use to forensic anthropologists. Materials and Methods: For the study, 60 dry adult human tali (24 left and 26 right) were obtained from the Department of Anatomy, SGT Medical College, Budhera. The morphometry of talar surfaces was done using a digital caliper accurate to 0.01 mm and data was recorded. Results: The mean values of medial, central and lateral length on the trochlear surface were 27.0cm, 28.1cm, 27.4cm on right side and 29.4cm, 27.0cm, 29.1cm on left side. Mean anterior, central and posterior widths on the trochlear surface were 27.6cm, 26.2cm, 21.1cm on right side and 27.0cm, 24.0cm, 23.1cm on left side. The mean central height and width on the lateral articular surface was 26.2 cm and 21.9 cm on the right side respectively and 23.0 cm and 16.8 cm on the left side respectively. The mean central height and central width on the medial articular surface was 13.6 cm and 25.9 cm on the right side respectively and 10.8cm and 17.9 cm on the left side respectively. Conclusions: The current study would be helpful as an important tool for reconstruction surgeries of hindfoot deformities and foot reconstruction procedures. Also it would be useful to orthopaedicians to design accurate talus bone prosthesis and talar implants. Morphometry of talus will be of use in objective categorization and race determination for forensic purposes.